Perceptionof volunteering by students – future employees in the context of building social responsibility in a workplace - Kulig-Moskwa, Katarzyna; Strzelczyk, Agata; Pijet-Migoń, Edyta (Research Papers of Wrocław University of Economics, 2018)
The aim of the paper is to show, how students perceive volunteering, what are their motivations and which activities they undertake most often. In addition, the study aims to investigate whether the notion of ‘corporate volunteering’ is known and understood. The target group consists of students of the WSB University, studying Finances and Accounting and Tourism and Leisure. The applied measurement technique was a distributed survey. The results show that students are aware of benefits arising from volunteering, but their own involvement is limited. Less than 4 per cent of respondents took voluntary jobs while studying. Students do not really know the term ‘corporate volunteering’, even if the majority has some experience in working full-time. The results indicate the necessity of action in this respect ,including educational one, since students’ attitudes, i.e. future or even current employees, will translate into building of CSR and, in the long term, shaping of the civil society
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 520; s. 91-105
Keywords: olunteering; employees volunteering; students volunteering; CSR; wolontariat; wolontariat pracowniczy; społeczna odpowiedzialność biznesu